Determinants of Food Delivery Apps (FDA) adoption reluctance among Generation Y in Malaysia - Liew, Serene; Wang, Li Jian; Hong, Syuan Ying; Go, Wei Nie (2021)
The food industry may not be the industry most affected by the COVID-19 pandemic, but it is apparent that many retail outlets have caused their owners to be at their wit’s end. But the ones who persist had to change their perspective and integrate with the online application market, thus came the FDA. Technology has yet again proven to be beneficial to all industries. Thus, the Technology Acceptance Model (TAM) was used to investigate human behaviour and their intentions by simulating how users accept and adopt the technology. Using their model as a reference the factors used are social influence, perceived risks, and features of mobile applications. It also includes a moderator which will be used to investigate the relationship it has toward the factors subsequently the reluctance behaviour. These factors would be the pillar of what affects perceived ease of use and perceived usefulness, followed by the intentions that can lastly manipulate behaviour (reluctance). Six hypotheses were developed in hopes of identifying the relationship the factors have towards reluctance behaviour as well as the moderator. Questionnaires were prepped and readily disseminated using online forms to 160 respondents within the millennial generation. The results that were decoded and analysed using SmartPLS were rather intriguing but would require further research to solidify the theories. Not least, managerial implications were proposed in hopes that future researchers, policy makers, and practitioners can be utilized as a reference for further experimental methodologies in improving the current state for online FDA in Malaysia.